Phytochemistry, pharmacological effects and mechanism of action of volatile oil from Panax ginseng C.A.Mey: a review - Xu, Yanan; Bian, Shuai; Shang, LiYing; Wang, Xin; Bai, Xueyuan; Zhang, Wei (Frontiers in Pharmacology, 2024)
Panax ginseng (P. ginseng), a traditional and highly valued botanical drug, has been used for thousands of years and is known around the world for its uses in food, medicine, and healthcare. The comprehensive study of P. ginseng is crucial for the quality assurance of medicinal materials and optimal resource utilization. Despite being present in trace amounts, P. ginseng volatile oil has a wide range of chemical metabolites with important medicinal potential. The volatile oil has shown promise in defending the cardiovascular system, as well as in terms of its ability of antibacterial, anti-aging, anti-platelet coagulation, anti-inflammatory, support the nervous system nutritionally, and shield it from harm. Due to its low composition and lack of thorough investigation, P. ginseng volatile oil’s therapeutic applicability is still restricted although it exhibited many benefits. This review aims to provide insights into the chemical composition, extraction processes, pharmacological effects, and mechanisms of action of P. ginseng volatile oil, and to provide theoretical support and guidelines for future research and clinical application.